Operationalizing food security in IFAD projects: an introduction: Technical Guide: Strengthening the Household Food Security and Nutritional Aspects of IFAD Poverty Alleviation Projects: Developing Operational Methodologies for Project Design and Monitoring - Hoddinott, John F. (International Food Policy Research Institute, 1999)
This is an introductory guide in two senses. First, it provides a brief introduction to the concept of food security. (An introduction to nutrition issues is found in Technical Guide #5.) It outlines the links between the types of projects often designed and their impact on food security and nutrition. By doing so, it provides a framework for thinking about what projects would be most appropriate in a given situation and indicates what types of information are needed in order to maximize impact on food security. It can also be the case that collaborators in developing countries are not always fully conversant with food security concepts. The material presented in this guide can also be used to sensitize such individuals. Second, it introduces the remaining ten guides, showing how using these can assist in easing information constraints often faced by development practitioners.